Green HRM for sustainable aviation: An integration evaluation using PLS-SEM and fsQCA - Dewi Puspaningtyas Faeni; Ratih Puspitaningtyas Faeni; Basrowi; Sungkono (Environmental Challenges, 2025)
This study examines the impact of Green Human Resource Management (GHRM) practices on Green Organizational Culture, Employee Green Behavior, and Carbon Emission Reduction in the aviation industry. Given the industry's significant environmental footprint, integrating sustainable HR practices is essential. Using a quantitative approach, data were collected through an online survey targeting employees involved in HR, sustainability, and operations. Participants were deliberately chosen using purposive sampling to ensure they possessed the necessary expertise. To test the hypothesized relationships and explore complex causal configurations, a hybrid methodological approach was adopted, combining Partial Least Squares Structural Equation Modeling for theory testing with Fuzzy-Set Qualitative Comparative Analysis to identify alternative pathways leading to carbon emission reduction outcomes. Findings reveal that Green Training & Development, Green Performance Management, and Green Organizational Culture significantly influence Employee Green Behavior and Carbon Emission Reduction. However, Green Compensation & Rewards does not directly impact Employee Green Behavior but has an indirect effect through mediation. These results align with previous research on GHRM and sustainability but highlight industry-specific challenges. Theoretical implications extend existing GHRM models by emphasizing mediation effects, while practical implications suggest targeted HR policies for sustainable aviation. Limitations include reliance on self-reported data and the study’s focus on a specific industry. Despite this, the research offers valuable insights into effective HR strategies for enhancing environmental performance in aviation.